2006
DOI: 10.1248/jhs.52.781
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Effects of Verapamil on Ethanol-Induced Gastric Lesions in Rats

Abstract: The effects of graded doses of verapamil on ethanol-induced stomach mucosal damage were studied in rats. Gastric lesions were induced in vivo by oral administration of 80% ethanol and evaluated with regard to ulcer index, gastric mucus content, free and total acidity, lipid peroxidation and nonprotein sulfhydryl groups. Orally administered ethanol markedly increased the ulcer index and lipid peroxidation. Pretreatment of rats with verapamil (1, 5, and 25 mg/kg i.p.) was carried out 1 h before the administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…All these reductions were found to be statistically highly significant when compared with Carbachol alone. Our study is consistent with other workers who concluded that Verapamil significantly reduces gastric acid secretion (Kadalmani et al 2011;Kilie et al 2006). Verapamil, a well known calcium channel blocker inhibits the calcium influx, which may be responsible for the observed reductions in volume and acidity of gastric secretion.…”
Section: Discussionsupporting
confidence: 94%
“…All these reductions were found to be statistically highly significant when compared with Carbachol alone. Our study is consistent with other workers who concluded that Verapamil significantly reduces gastric acid secretion (Kadalmani et al 2011;Kilie et al 2006). Verapamil, a well known calcium channel blocker inhibits the calcium influx, which may be responsible for the observed reductions in volume and acidity of gastric secretion.…”
Section: Discussionsupporting
confidence: 94%
“…The results of this study shows that amlodipine in dose of 0.5 mg/kg demonstrates anti-ulcer action in different etiologies of peptic ulcers. Similar observations were reported by Kilic et al .,[ 6 ] with verapamil in ethanol-induced gastric ulcer model and Jain et al .,[ 9 ] with verapamil and diltiazem. One previous study has demonstrated ulcer protective efficacy of amlodipine in doses 0.5 mg/kg and 1 mg/kg in pylorus ligation model in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol-induced gastric ulcer: The study medications were administered 1 hour prior to induction of ulcer with ethanol (80%, 1 ml/100 gm) orally. [ 6 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Dihydropyridine CCB are reported to enhance production of NO whereas as verapamil did not have any effect on NO in vitro. 12 Diltiazem is a calcium channel blocker of non-dihydropyridine type. 5 In present study, diltiazem has the property of ulcer preventing activity in diclofenac induced gastric ulcers.…”
mentioning
confidence: 99%